Soil properties comparison of lime treated soft clay - Amir Saifuddin, Amram (2015)
The main objectives of this research are to determine the plasticity properties and the shear strength properties of lime treated soft clay. The physical properties and shear strength properties of lime treated soft clays are investigated by conducting laboratory test such as atterberg limit test and unconfined compression test. Atterberg limit test have been carried out for 7 days of curing period for the treated clay with the optimum lime content. For unconfined compressive test, the test have been carried out for 7, 14, and 28 days of curing period. For atterberg limit, there is an increment in both plastic and liquid limit of the lime treated soft clay and untreated soft clay. The liquid limits for untreated soil is 66.5% then increase into 73.30% when 20% lime is added. The plastic limit for untreated soil sample is 34.9% before it increase to 38.68% for 20% lime added respectably. This resulted an increment in plasticity index from 31.55% for untreated sample to 34.62% at 20% lime. For unconfined compressive test, the result have shown that there is an increment for the axial stress based on the curing days. The maximum axial stress for the untreated clay is initially 158.47 kN/m2. After added with 20% of lime content, the maximum axial stress is increased to 209.21 kN/m2 for 7 days of curing while for 14 and 28 days, the maximum axial stress are 231.19 kN/m2 and 352.02 kN/m2. It can be conclude that, lime stabilization method can be used as a soil treatment program for soft clay especially for road construction.